Atgimusios lietuviškos spaudos tradicijos Vilniuje 1904-1914 metais - Černiauskaitė, Violeta (Knygotyra, 2005)
This article aims to analyze the system of press supervision and control in interwar Lithuania, most often referred to as censorship. According to the subordination of the controlling authority and the limits of its responsibility, censorship falls into two categories: state (general and/or war) and church censorship. This article analyzes state censorship that existed between 1918 and 1940. This censorship is analyzed first of all bearing in mind war censorship, which was present in interwar Lithuania between 1919 and 1933. War censorship is established in the country when mobilization or a state of war is announced or during the war. It aims to prohibit the announcement of war-type data, events, etc., which could harm the affairs of the country’s armed forces. Though the term "war censorship" has not been mentioned either in the "Particular State Protection Statute" or in Press Laws, war censorship existed in Lithuania from 1919 till 1933. The issues of war censorship were solved by the Ministry of Defence, which had the right to appoint war commandants. When social democrats and peasant populists gained power, the state of war was canceled and censorship was eliminated with it. The censorship mechanism of the analyzed period was operating on two levels: state and local. At the state level, press supervision and control functions were carried out by the Ministry of Interior. At the local level, censorship was assigned to County Governors and war commandants. On 1 April 1933, the position of war censor at the Ministry of Defence was repealed. Though war censorship was eliminated, the heads of printing houses still had to submit the first three copies of one-time and periodical printings to war commandants before the publications were issued. This means that censorship remained, but it was functioning in another form—the publication did not contain a seal "Permitted by War Censorship." In 1938, the Public Work Management, run by the Prime Minister’s office, was established. In addition to the supervision of the printings of periodicals, it carried out the control of non-periodical printings. In April 1939, the Public Work Management was liquidated, and its functions were commissioned to the Press and Associations Department under the supervision of the Ministry of Interior. This department registered the publications issued in Lithuania and abroad. This institution had a press supervision archive and a library for storing the printings, which were both prohibited and not prohibited by censorship.